Chlamydia psittaci pneumonia - evolutionary aspects on chest CT - Na Yang; Zhengqiu Ou; Qian Sun; Junping Pan; Jing Wu; Chen Xue (BMC Infectious Diseases)
Abstract Purpose To present the different findings of Chlamydia psittaci (C. psittaci) pneumonia on computed tomography (CT) according to the progression of the disease, to improve diagnostic accuracy, guide early clinical diagnosis, evaluate treatment efficacy, and reduce the mortality associated with the disease. Methods In total, 80 cases of C. psittaci pneumonia diagnosed through next-generation sequencing from January 2019 to December 2023 in multiple hospitals in China were collected according to the inclusion criteria and analyzed. The study discussed important CT findings and their dynamic changes. Results The most common manifestations of C. psittaci pneumonia are lobar pneumonia and spherical pneumonia types with interstitial changes. The most common signs are the intralobular lines, air bronchogram sign, and reverse halo sign. In addition, necrosis, cavitation, and the tree-in-bud sign are rare but often associated with pleural effusion and splenomegaly. In the ultra-early stage, vascular inflammation changes were observed on imaging, often manifesting as ground-glass opacities around small core vessels or thickening of pulmonary hilar vessels. In the early stage, secondary lobules showed high-density shadows, which rapidly fused into large areas in the progressive stage, easily forming lobar pneumonia. The repair and absorption period tended to show the formation of the reverse halo sign centrally, and the dissipation period might have led to the formation of fibrous bands. Conclusion Combining clinical manifestations, laboratory tests, contact history, and imaging findings contribute to the diagnosis of C. psittaci pneumonia.